THE POLITICS OF SECULARITY/RELIGIOSITY IN KAZAKHSTAN - BIZHANOV, Akhan; AMREBAEV, Aydar; BUROVA, Elena; SEITAKHMETOVA, Natalya (CENTRAL ASIA AND THE CAUCASUS, 2019)
In Kazakhstan, the religious situation, with its steadily growing impact on social development, mentality, and lifestyle, is unfolding spontaneously. Expert discussions of religious influence and the degree of clericalization of secular society are multifaceted and highly contradictory. State politics and the state structure responsible for interaction with religious institutions are in a state of perpetual transformations, which adds turbulence to the situation and makes the implementation of different scenarios of changes in the religious (mainly Islamic) landscape possible. The state responds to the threat of radicalization of society using quasi-religious patterns, employing force, preventive educational efforts, and rehabilitation of certain groups within the republic’s population. Overall, the balance between secularity and religiosity requires a consistent and non-contradictory state policy.